2021
DOI: 10.1097/ju.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping the Association between Nocturia and Hypertension: A Systematic Review and Meta-Analysis

Abstract: The association between nocturia and hypertension has been widely reported yet remains poorly characterized, precluding a more refined understanding of blood pressure as it relates to the clinical urology setting. We synthesized current evidence on the relationship between nocturia and hypertension as a function of nocturia severity, age, gender, race, body mass index and diuretic use. Materials and Methods: We searched PubMedÒ, EMBASEÒ and Cochrane databases for studies published up to May 2020. Random effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Notably, the present study models explain only a fraction of the variance observed in the response variable (Nagelkerke R 2 ≤ 0.0985 across all models), suggesting that other variables are of larger importance. While current evidence supports the use of a 1‐void threshold for nocturia as employed in the present analysis, 14,15 there exists no consensus as to the optimal nocturnal voiding cutoff in nocturia research, 27 and it stands to reason that different criteria may differentially affect outcomes. Although the study sample was representative of the patient population treated at our institution, the present results may be biased by the disproportionate number of African‐Americans, females, and comorbidity burden, such that future studies are needed to determine whether the present study findings may be generalized to meaningfully characterize the relationship between nocturia and hypertension in other clinical and community settings.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Notably, the present study models explain only a fraction of the variance observed in the response variable (Nagelkerke R 2 ≤ 0.0985 across all models), suggesting that other variables are of larger importance. While current evidence supports the use of a 1‐void threshold for nocturia as employed in the present analysis, 14,15 there exists no consensus as to the optimal nocturnal voiding cutoff in nocturia research, 27 and it stands to reason that different criteria may differentially affect outcomes. Although the study sample was representative of the patient population treated at our institution, the present results may be biased by the disproportionate number of African‐Americans, females, and comorbidity burden, such that future studies are needed to determine whether the present study findings may be generalized to meaningfully characterize the relationship between nocturia and hypertension in other clinical and community settings.…”
Section: Discussionmentioning
confidence: 82%
“…As LVH, LAE, and QTC prolongation are all characteristic of hypertension, a threshold of ≥1 void per night was predefined for nocturia in view of prior literature on 24-h ambulatory blood pressure monitoring, which has identified a pronounced difference in nocturnal blood pressures between subjects with zero versus 1 nocturnal void, 14 as well as population-level evidence of a significant association between hypertension and ≥1 nocturnal voids. 15 Univariate associations between the aforementioned covariates and the presence of nocturia were explored. The Cochran-Mantel-Haenszel test was used to measure to strength of the association between nocturia and LVH, LAE, and QTc prolongation after stratifying on the basis of age.…”
Section: Methodsmentioning
confidence: 99%
“…The initial search yielded 767 entries, of which 322 were excluded that were not SRs. Of the 445 SRs identified, 60 met the eligibility criteria [ 7 66 ]. Out of the 60 studies, 11 studies [ 56 66 ] (18.33%) did not report on outcome-specific rating, which refers to certainty of evidence of individual studies was assessed or overall certainty of the body of evidence was rated (Supplementary Table S 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 445 SRs identified, 60 met the eligibility criteria [ 7 66 ]. Out of the 60 studies, 11 studies [ 56 66 ] (18.33%) did not report on outcome-specific rating, which refers to certainty of evidence of individual studies was assessed or overall certainty of the body of evidence was rated (Supplementary Table S 1 ). Therefore, a total of 49 SRs (81.67%) that rated the outcome-specific certainty of evidence were included in our methodologic survey.…”
Section: Resultsmentioning
confidence: 99%
“…3 The condition is associated with various morbidities, such as obesity, diabetes, hypertension, cardiac disease, and depression; these morbidities may contribute to a higher risk of mortality. [4][5][6] Cold exposure results in lower urinary tract symptoms (LUTS). Previously, low ambient temperature-induced detrusor overactivity in rats was found to be correlated with decreased skin temperature.…”
Section: Introductionmentioning
confidence: 99%